Drug–drug plasma protein binding interactions of ivacaftor. Issue 6 (24th February 2015) - Schneider, Elena K.; Huang, Johnny X.; Carbone, Vincenzo; Baker, Mark; Azad, Mohammad A. K.; Cooper, Matthew A.; Li, Jian; Velkov, Tony
Abstract : Ivacaftor is a novel cystic fibrosis (CF) transmembrane conductance regulator (CFTR) potentiator that improves the pulmonary function for patients with CF bearing a G551D CFTR‐protein mutation. Because ivacaftor is highly bound (>97%) to plasma proteins, there is the strong possibility that co‐administered CF drugs may compete for the same plasma protein binding sites and impact the free drug concentration. This, in turn, could lead to drastic changes in the in vivo efficacy of ivacaftor and therapeutic outcomes. This biochemical study compares the binding affinity of ivacaftor and co‐administered CF drugs for human serum albumin (HSA) and α1 ‐acid glycoprotein (AGP) using surface plasmon resonance and fluorimetric binding assays that measure the displacement of site‐selective probes. Because of their ability to strongly compete for the ivacaftor binding sites on HSA and AGP, drug–drug interactions between ivacaftor are to be expected with ducosate, montelukast, ibuprofen, dicloxacillin, omeprazole, and loratadine. The significance of these plasma protein drug–drug interactions is also interpreted in terms of molecular docking simulations. This in vitro study provides valuable insights into the plasma protein drug–drug interactions of ivacaftor with co‐administered CF drugs. The data may prove useful in future clinical trials for a staggered treatment that aims to maximize the effective free drug concentration and clinical efficacy of ivacaftor. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Ivacaftor is a first‐of‐its‐kind cystic fibrosis (CF) drug. Because ivacaftor is highly bound (>97%) to plasma proteins, co‐administered CF drugs may compete for plasma protein binding sites and impact the free drug concentration. This study compares the plasma protein binding affinity of ivacaftor and co‐administered CF drugs. The data may prove useful in future clinical trials of a staggered treatment regimen that aims to maximize the effective free drug concentration and clinical efficacy of ivacaftor.